MIDWIFERY CARE ON THE PREGNANT WOMEN IN LAMPREH LAMTEUNGAOH, INGIN JAYA, THE DISTRICT OF ACEH BESAR: - Fidiatul Khairi; Kartinazahri; Juliastuti (Department of Midwifery, Health Polytechnic of Aceh, 2024)
Health issues that often occur during pregnancy include anemia, Chronic Energy Deficiency (CED), and obesity; risk factors such as closely spaced pregnancies, multiple pregnancies/twins, obstetric complications, non-communicable and communicable diseases, and mental health issues need more attention because they significantly impact overall health. One of the indicators of public health status is the maternal mortality rate and infant mortality rate. The higher the Maternal Mortality Rate (MMR) and infant mortality in a country, the worse the health status of that country is likely to be. This case report aims to provide midwifery care for pregnant women in Gampong Lampreh Lamteungoh, Ingin Jaya Subdistrict, Aceh Besar District, and to document it in the SOAP format. The first care was conducted on Tuesday, January 24, 2023, and after data collection, it was found that the mother had no complaints. The examination results were within normal limits. The data analysis indicated G1P0A0 at 27 weeks and 1 day of pregnancy, with both mother and fetus in good condition. Midwifery guidance was provided regarding recommendations for nutritious food, adequate water intake, sufficient rest, a continuation of iron supplement tablets, health education on discomfort during pregnancy, and visiting health facilities if any complaints arise. According to her concerns, further care will be provided during the mother's next visit.